Diversifying and Benchmarking Madagascar - Thorvaldur Gylfason; Jean-Pascal N. Nganou (CESifo GmbH, 2024)
Because excessive specialization can be risky, diversification matters for sustainable development. A case study of Madagascar, this paper begins by briefly discussing economic and institutional diversification and presenting a simple model of production possibilities to illuminate the possible contribution of diversification to economic and social development in Madagascar and elsewhere. By comparing Madagascar with its peers, the paper aims to identify policies and strategies that can foster economic and institutional diversification and to suggest pathways for Madagascar to promote the welfare of its people through diversification, aiming also to mitigate climate change and its consequences.
Keywords: O11; O13; O15; 330; diversification; institutions; economic growth; natural resources; climate change